Structural school safety measures, SROs, and school-related delinquent behavior and perceptions of safety: A state-of-the-art review. Issue 3 (15th August 2016) - Reingle Gonzalez, Jennifer M.; Jetelina, Katelyn K.; Jennings, Wesley G.
Abstract : Purpose: The purpose of this paper is to examine the impact of school safety measures, including SROs and safety personnel, on school-related delinquency and perceived safety. Design/methodology/approach: Specifically, a comprehensive search of the literature was performed to identify studies published between January 1, 1998 and July 1, 2016 that focussed on structural school safety measures such as metal detectors, cameras, closed circuit television systems, and access control measures and/or school resource officers in primary and secondary schools. Only studies that relied on randomized controlled trials and pre-test/post-test designs evaluating the impact of at least one school safety measure in reference to a control condition were eligible for inclusion. Findings: The results of this exhaustive search revealed 32 unique study samples that met the inclusion criteria. Results from the studies suggest that implementation of more security measures may not be an effective policy. More safety measures often result in a decline of student-perceived safety. Study limitations and directions for future research are also discussed. Originality/value: Results from this meta-review can provide educational administrators, superintendents, and school safety policymakers with a synthesis of only the most rigorous and valid studies that evaluate the impact of school safety measures on both actual and perceived school-related delinquency and safety. This information will provide school safety decision makers with a state-of-the-art synthesis of how school safety measures impact school-related delinquency problems and safety, and which measures appear to be most effective for informing the allocation of scarce resources.